Poly(2-oxazoline)s One-Pot Polymerization and Surface Coating: From Synthesis to Antifouling Properties Out-Performing Poly(ethylene oxide) - Svoboda, Jan; Sedláček, Ondřej; Riedel, Tomáš; Hrubý, Martin; Pop-Georgievski, Ognen (Biomacromolecules, 2019)
Poly(2-alkyl-2-oxazoline)s (PAOx) represent a class of emerging polymers that can substitute or even outperform poly(ethylene oxide) (PEO) standard in various applications. Despite the great advances in PAOx research, there is still a gap in the direct experimental comparison of antifouling properties between PAOx and the golden standard PEO when exposed to blood. Motivated by this, we developed a straightforward protocol for the one-pot PAOx polymerization and surface coating by a “grafting to-” approach. First, we synthesized a library of hydrophilic poly(2-methyl-2-oxazoline)s (PMeOx) and poly(2-ethyl-2-oxazoline)s (PEtOx) with molar mass ranging from 1.5 to 10 kg/mol (DP = 16–115). The PAOx living chains were directly terminated by amine and hydroxyl groups of polydopamine (PDA) anchor layer providing the highest so far reported grafting densities ranging from 0.2 to 2.1 chains/nm2. In parallel, PEO chains providing the same degree of polymerization (molar mass from 1.2 to 5 kg/mol, DP = 28–116) bearing thiol groups were grafted to PDA. The thickness, surface-related parameters, covalent structure, and antifouling properties of the resulting polymer brushes were determined via various surface sensitive techniques. The comparison of the synthesized PAOx and PEO brushes led us to the conclusion that at the same surface-related parameters, PMeOx brushes show significantly better antifouling character when challenged against human blood plasma.